Minimization of Wound With the Assistance of a Needle Grasper in Single-Incision Laparoscopic Appendectomy. (October 2019) - Kim, Beom-Jin; Kim, Jong Won; Choi, Yoo Shin; Park, Yong Gum; Kim, Beom Gyu; Park, Joong-Min; Lee, Seung Eun; Park, Byung Kwan; Suh, Suk Won; Chi, Kyong-Choun
Background. Technical difficulties and pain from large wounds have prevented the widespread use of single-incision laparoscopic appendectomy (SILA). This study aimed to evaluate the efficacy of our newly developed needle grasper (Endo Relief)-assisted SILA (NASILA). Methods. For NASILA, about a 12-mm umbilical incision was made, and a glove port was introduced. A needle grasper was then introduced through a 2.5-mm wound on the suprapubic area. For SILA, a 2.5-cm transumbilical wound was made. The medical records of patients who underwent SILA or NASILA from June 2017 to September 2017 were retrospectively reviewed. Operative and short-term postoperative outcomes and results of telephone interviews for scars were compared. Results. A total of 49 patients in the SILA group (male: 40.8%) and 12 in the NASILA group (male: 50.0%) were included. Appendicitis status (not perforated:perforated without abscess:perforated with abscess) was significantly different between the 2 groups (SILA vs NASILA, 30:18:1 vs 4:6:2, P = .027). Additional trocars were inserted in 9 patients (18.4%) of the SILA group. The operative time was significantly shorter (43.3 ± 33.6 vs 54.1 ± 15.6 minutes, P = .012), and the highest numerical pain intensity score during the first 24 hours after surgery was significantly lower (2.4 ± 0.7 vs 3.0 ± 0.9, P = .038) in the NASILA group than in the SILA group. Hospital stay, postoperative complications, and complaint of scar were not significantly different between the 2 groups. Conclusions. NASILA was not inferior to SILA regarding cosmetic results. Operative convenience is higher in NASILA than in SILA, and the smaller surgical wound in NASILA minimizes postoperative pain.